Scripture as popular text. - Tanner, Kathryn (Modern Theology)
Presents information on contemporary theology in relation to Christian claims about the universal and permanent pertinence of Scripture. Indepth look at theological and literary claim of value; Details on the basic understanding of universal permanence; Information on the timeless aspect of biblical text.